Tragedy and the tragic: a study of Ernst Hemingways A Farewell to Arms and Naguib Mahfouzs The Beginning and the End - Chelihi, Rania Khelifa; Latiff Azmi, Mohd Nazri; Jujar Singh, Hardev Kaur; Somia, Ayaicha (Canadian Center of Science and Education, 2018)
This paper is a comparative study between Ernst Hemingway’s A Farewell to Arms and Naguib Mahfouz’s The Beginning and the End, paralleled with the authors’ concepts of tragic vision; based on the development of the theory of tragedy from Aristotle to Hegel as well as the personal philosophy of life as tragedy of both authors. Based on the researcher knowledge, tragedy concept in the selected novels is rarely and insufficiently highlighted by few scholars and critics. Moreover, it is a comparison of novels from different cultures—Arabic literature and literature in English—in order to bridge the gap between them. The novels are stories where every day moral dilemmas often present profound paradoxes with which heroes and heroines must deal. Tragedy, in the same vein, is such a paradoxical story where we have to deal at any rate with our everyday moral dilemmas, where we are sometimes called upon to make difficult choices not between right and wrong, but between what we might define as two rights. Hegelian concept of tragedy focused on dissension and war of dichotomies between good and bad, as well as what is right and what is wrong. The tragic elements in the two novels make them Hegelian tragedies par excellence.